Preparation, Characterization, and Photocatalytic Properties of CaNb2O6 Nanoparticles - Cho, In-Sun; Bae, Shin Tae; Yim, Dong Kyun; Kim, Dong Wan; Hong, Kug Sun (WILEY, 2009)
CaNb2O6 nanoparticles with a size range of 30-50 nm were synthesized by heat treatment at 600 degrees C after a solvothermal process and their optical and photocatalytic properties were investigated. The prepared powders were characterized by X-ray powder diffractometer, field-emission scanning electron microscope, transmission electron microscope, UV-Vis diffuse reflectance spectroscopy, Fluorescence spectroscopy, and Raman spectroscopy. Compared with a powder of the same material prepared by a solid-state reaction (SS) method, the nanoparticles exhibited a higher Brunauer-Emmett-Teller (BET) surface area, more efficient light absorption, and enhanced photocatalytic activity for producing H-2 from pure water under UV irradiation. The photoluminescence spectra revealed that a radiative recombination process is dominant in the powder prepared by the SS method (strong blue emission at 300 K) under UV light irradiation, while no obvious emission was observed in the nanoparticles. This decrease of the radiative recombination as well as the higher optical absorption ability and higher BET surface area resulting from the reduced dimensionality led to enhanced photocatalytic activity of the nanoparticles.
Keywords: PARTICLE-SIZE; NANOSTRUCTURES; LUMINESCENCE; NI